2014
DOI: 10.1103/physrevlett.112.086802
|View full text |Cite
|
Sign up to set email alerts
|

Electric Field Tuning of the Rashba Effect in the Polar Perovskite Structures

Abstract: We show that the Rashba effect at the polar perovskite surfaces and interfaces can be tuned by manipulating the two-dimensional electron gas (2DEG) by an applied electric field, using it to draw the 2DEG out to the surface or push it deeper into the bulk, thereby controlling the surfacesensitive phenomenon. These ideas are illustrated by a comprehensive density-functional study of the recently-discovered polar KTaO3 surface. Analytical results obtained with a tight-binding model unravel the interplay between t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
96
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(99 citation statements)
references
References 20 publications
(12 reference statements)
2
96
1
Order By: Relevance
“…Tight-binding calculations have shown that the d xy , d xz , and d yz orbitals all give rise to a linear Rashba-type splitting 29,32,33 , so the above frequencies and effective masses can be used to estimate the Rashba-type coupling constant responsible for the splitting of the hybridized d xz+yz band. In order to properly model the properties of the hybridized d xz+yz band, we extended the tight-binding model described by Rödel et al 34 to include a linear Rashba-type splitting (see Supplementary Note 5).…”
Section: Resultsmentioning
confidence: 99%
“…Tight-binding calculations have shown that the d xy , d xz , and d yz orbitals all give rise to a linear Rashba-type splitting 29,32,33 , so the above frequencies and effective masses can be used to estimate the Rashba-type coupling constant responsible for the splitting of the hybridized d xz+yz band. In order to properly model the properties of the hybridized d xz+yz band, we extended the tight-binding model described by Rödel et al 34 to include a linear Rashba-type splitting (see Supplementary Note 5).…”
Section: Resultsmentioning
confidence: 99%
“…The polar discontinuity at the LAO/STO interface leads to a rather strong Rashba-type SOC [7] and is considered to play an important role with respect to interfacial conductivity [8].…”
Section: Introductionmentioning
confidence: 99%
“…41 In the present case of BP, however, since the SOC is small and the energies of the p x and p y states that would spinorbit couple to the p z orbitals making up the valence and conduction band extrema are far away in energy, the pseudospins are nearly spin pure states |p z ↑ and |p z ↓ .…”
Section: Electric Field and Rashba Effectmentioning
confidence: 99%
“…These ideas are well known in the literature and developed further in our recent work on Rashba effect in the d electron solids. 36,41 Rashba Hamiltonian (Anisotropic case) -Now, consider the case with an anisotropic mass, with the effective mass tensor [m * −1 ( k)] ij =h −2 ∂ 2 ε( k)/∂k i ∂k j and the velocity v i =h −1 ∂ε( k)/∂k i =h j [m * −1 ] ij k j . A straightforward generalization of the isotropic case yields the desired anisotropic Rashba Hamiltonian…”
Section: Electric Field and Rashba Effectmentioning
confidence: 99%